Sports biomechanics and motor control research group: Aerial movement - Twisting somersaults - Yeadon, M. R. (2004)
Sports biomechanics seeks to gain an understanding of the mechanics of sports movements. Such questions as how the approach speed, leg plant angle and knee angle affect high jumping performance may be addressed experimentally. Questions such as why high jumpers use a curved approach may be answered using computer simulation modelling. Both approaches are evident in the research articles listed in the Group's pages.